On the Role of the Stable Plasminogen Activator of the Venous Wall in Occlusion Induced Fibrinolytic State - Constantini, R; Spöttl, F; Holzknecht, F; Braunsteiner, H (Thrombosis and Haemostasis, 1969)
The fibrinolytic activity respectively the PA activity of normal veins before and after venous occlusion is measured by the histochemical method of Todd. The results show marked decreases of PA of the adventitia and an increase of PA of the endothelial type, after venous occlusion. This suggests a transfer of PA through the venous wall into the intravascular lumen, and may be the cause of increased fibrinolytic activity in venous blood after occlusion. Contrary assumptions are discussed.